Chemotherapy beyond first-line in stage IV metastatic non-small cell lung cancer - Younes,Riad Naim (2011)
OBJECTIVE: Platinum-based doublet chemotherapy is considered the standard of care for advanced non-small cell lung cancer (NSCLC). However, prognosis after recurrent or progressive disease following first-line chemotherapy is usually poor. Maintenance chemotherapy, second line treatment and even third line chemotherapy are available for patients with advanced NSCLC. Unfortunately, few patients are candidates for chemotherapy beyond first line. The present study evaluated characteristics of patients with NSCLC and outcomes of the treatment of their metastatic disease, with emphasis on second and third-line chemotherapy. METHODS: This was a retrospective observational study of 2,673 patients with metastatic, stage IV, non-small cell lung cancer admitted for treatment in two São Paulo institutions. First-line chemotherapy was defined as the first chemotherapeutic approach administered to the patient. Second and third-line chemotherapy were defined as the systemic treatment administered after discontinuing first-line chemotherapy, either for intolerance or for progressive or recurrent disease. RESULTS: Most patients (57.9%) received first-line chemotherapy, and approximately 23.4% received second-line and 8% third-line regimens. Only 2.5% received fourth-line chemotherapy. Median overall survival (OS) was 8 months (95% CI: 8-9 months). At univariate analyses, gender (p < 0.05), histology, first-line chemotherapy, objective response to first-line chemotherapy and second-line chemotherapy (p < 0.01) were prognostic factors related to overall survival. At multivariate analysis, only performance status (p = 0.04), receiving any second-line chemotherapy (p < 0.01) and response to first-line chemotherapy (p < 0.01) were independent predictors of overall survival. CONCLUSION: Second-line chemotherapy is a therapeutic strategy that should be considered for a selected group of patients. Performance status and response to first-line chemotherapy could be determinant characteristics to select patients who might be treated beyond first-line chemotherapy.